Universalisation versus targeting in maternal and child health care provisioning: Evidence from India - Sohini Paul; Sourabh Paul; K.S. James (Elsevier, 2019)
To eradicate the persistent inequality in utilisation of Maternal Health Care Services (MHCS), India's Government has adopted various programmes under the National Rural Health Mission (NRHM) in 2005. The Janani Suraksha Yojana (JSY), a demand-side intervention, is one of the flagship programmes under the NRHM. Using two rounds of the nationally representative National Family Health Survey (NFHS) data collected in 2005-06 and 2015-16, respectively, we attempt to map the extent to which inequality in MHCS utilisation has changed over time across states after the implementation of NRHM; analyse whether there are differences in the patterns of inequality prevalent in the universal and targeted states; and find evidence to decide whether universalisation is more effective than targeting in reducing inequality in MHCS utilisation. We measure relative inequality and use the difference in difference technique to answer the research questions. For analysis, we have considered five outcome variables spanning across three stages of the continuum of care in maternal health. We find that relative inequality in MHCS utilisation declined across states during the period 2006-16, though in varying degrees. Universal states experienced a higher level of inequality as compared to the targeted states. However, universal states observed a higher decline in inequality over time relative to the targeted states controlling for other state-level characteristics. The study establishes that the programme implementation strategy and conditional cash transfer programmes influence the reduction of inequality in MHCS utilisation. This study makes an important contribution to the literature on public health policy and inequality in health care utilisation by highlighting the differential impact of universalisation and targeting on reducing inequality in the use of MHCS. Keywords: Inequality, Maternal health care services, Janani suraksha yojana, Indian states, Universalisation, Targeting, JEL classification: I18, I38